2023
DOI: 10.1167/tvst.12.7.22
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Imaging Predictors of Intermediate Age-Related Macular Degeneration Progression

Rita Flores,
Ana C. Fradinho,
Rita Serras Pereira
et al.

Abstract: Purpose Intermediate age-related macular degeneration (iAMD) is a risk factor for progression to advanced stages, but rates of progression vary between individuals. Predicting individual risk is advantageous for programing timely and effective treatment and for patient stratification into future clinical trials. Methods We conducted a prospective and noninterventional study following patients with iAMD for 24 months. Optical coherence tomography parameters related with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Recently iRORA has been proposed as a biomarker of intermediate AMD, however, as Wu et al suggested, iRORA is also a precursor of cRORA and therefore a predictive factor for GA development 57 . Furthermore, Flores et al identified iRORA as the factor with the higher probability of developing advanced AMD (OR 12.91) 58 …”
Section: Biomarkersmentioning
confidence: 99%
“…Recently iRORA has been proposed as a biomarker of intermediate AMD, however, as Wu et al suggested, iRORA is also a precursor of cRORA and therefore a predictive factor for GA development 57 . Furthermore, Flores et al identified iRORA as the factor with the higher probability of developing advanced AMD (OR 12.91) 58 …”
Section: Biomarkersmentioning
confidence: 99%
“…In general, standard OCT is used for the identification of iRORA lesions; nevertheless, high-resolution OCT has been superior in the detection and classification of the atrophic lesions, enhancing the assessment reliability. iRORA is a noteworthy OCT biomarker as these lesions are predecessors for GA and a high-risk progression factor to the advanced stages of AMD [128]. Another relevant aspect to note is that the term "nascent GA" can be used when iRORA lesions are present but there is no association with previous or present signs of macular neovascularization [152].…”
Section: Iroramentioning
confidence: 99%
“…The disruption of EZ is another OCT parameter which has been linked to the progression of AMD to advanced stages [11,64,99]. There is 2.5-fold risk increase of developing advanced stages of AMD in patients that present with EZ disruption compared to those without it [128]. EZ changes have been noticed as early as 4 years before GA onset [85].…”
mentioning
confidence: 99%
See 1 more Smart Citation